Horizontal and intersecting inequalities in Mozambique: 1997-2017 - Ricardo Santos; Eva-Maria Egger; Vincenzo Salvucci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study seeks to add to the research on inequality in least developed countries, namely in Mozambique, by measuring and mapping indicators of horizontal wealth inequality along geographic regions and ethnolinguistic identities. Using census data for 1997, 2007, and 2017, we identify possible intersecting inequalities, measuring between-group inequality along joint provincial-urban/rural-ethnolinguistic identities. Additionally, we find heterogeneous evolutions of group inequality between 1997 and 2017 among the country's eleven provinces. We find that, while there is a general improvement in the average household wealth indicators, there is a strong suggestion of increasing group inequalities between 1997 and 2017. Although this is manifest throughout the country, in general, there is evidence that the southern provinces may be experiencing a more equitable development. We find evidence that this evolution may be driven by an urban-rural decoupling, added to low internal migration. These are insights from correlates. No causal inference can be made from this analysis. However, the differences in average wealth between groups, if perceived, may feed grievances. They should be better understood so that underlying causes can be addressed.
Keywords: D31; D63; I32; O18; 330; inequality; horizontal wealth inequality; intersecting inequalities; wealth; Mozambique